Enviromental Socio-Economic Value for Capture Fisheries Resources at Jatigede Reservoir, Sumedang, West Java Province - Atikah Nurhayati; Titin Herawati; Walim Lili; Ayi Yustiati; Isni Nurruhwati Matindas (Jurnal Penyuluhan, 2020)
Sumedang District is one of the areas where Jatigede Reservoir is built, which is primarily for hydroelectric power generation and other derivative functions such as drinking water supply, irrigation, flood control, tourism, and capture fisheries. Research aims to examine how the potential of capture fisheries resources and socio-economic values for local communities. This method used quantitative description of the performance of costs and benefits. The data used in this reserach are primary data and secondary. Primary data with judgment sampling as many as 30 respondents. Based on the research gap analysis for the social aspects of the local communities affected by the construction of reservoirs Jatigede contradiction between the expectations of the people to utilize the reservoir Jatigede based derivative function with local government regulations, so there is still social conflicts in society.Results of Analytic Network Process levels of jatigede reservoir function based on economic value the main function of hydroelectric power plants is socio-economic value for residents affected by the construction of Jatigede reservoir, one of which is capture fisheries, which should be given by the local government regulations regarding catchment zones, types of fishing gear are allowed and security protection for fishing in reservoirs Jatigede, institutional strengthening Jatigede fishing in reservoirs.Environmental aspects by taking into account the aquatic habitat in the Jatigede reservoir,which can be used for fisheries with due respect to the conservation of fishery resources, especially for endemic fish by periodically restocking, so that socio-economic and environmental values can be synergistic in utilizing the Jatigede reservoir.